Design, synthesis and pharmacological evaluation of novel fluorescent ligands for the mu-opioid receptor - Marshall, William (2021)
The mu opioid receptor (MOR) belongs to the superfamily of G-protein coupled receptors (GPCRs) and remains an important target in the management of pain and addiction, with an emerging role in promoting tumour growth. Understanding of the complex role of the MOR in these signalling pathways would be aided by further study of receptor-ligand interactions. Development of fluorescent ligands to target the MOR may provide the necessary tools to study such receptor pharmacology and localisation in healthy and diseased tissue.